Bevacizumab treatment for neovascular age-related macular degeneration in the setting of a clinic: “real life” long-term outcome - Beykin, Gala (BMC Ophthalmol, 2015)
BACKGROUND: To evaluate the long-term outcome of bevacizumab therapy for neovascular age related macular degeneration (NVAMD) in the setting of a clinic. METHODS: Consecutive group of NVAMD patients who were treated in a single 3(rd) referral center with bevacizumab using a loading dosage of 3 monthly injections followed by variable dosing for at least 48 months were retrospectively evaluated. Genotyping was performed for CFH (rs1061170), HTRA1 (rs1200638), and C3 (rs2230199). Main outcome measures included functional and morphological treatment outcomes as well as their risk allele associations. RESULTS: Out of 128 patients who started bevacizumab treatment over 4 years before the study endpoint [mean (±SD): 60 ± 10.9 months], 75 eyes of 67 (52.3%) patients, were still followed. Mean best corrected visual acuity (BCVA) (LogMAR ± SEM) improved from 0.66 ± 0.07 at baseline to 0.48 ± 0.05 (p = 0.012) at 1 year, but deteriorated from the 3(rd) year on and at the final exam reduced to 0.69 ± 0.07 (p = 0.6, compared with initial BCVA). Macular thickness mirrored visual acuity (VA) changes showing initial thinning followed by thickening from the 3(rd) year on. Individuals carrying the CFH risk -allele had a mean thickening (microns ± SEM) of 66.9 ± 70.4 versus a mean thinning of 76.8 ± 22 in non-carriers (p = 0.015). CONCLUSIONS: Bevacizumab therapy for NVAMD using a flexible treatment algorithm in a “real life” clinical setting initially obtained VA gain and thinning of the macula that were maintained for two years, but were lost later on.